Energy its use and the environment - Hinrichs, Roger 1941-; Kleinbach, Merlin H. (Australia Brooks/Cole, Cengage Learning, 2013)
ENERGY: ITS USE AND THE ENVIRONMENT, Fifth Edition, emphasizes the physical principles behind energy and its effects on our environment. The text explains the basic physical principles behind the use of energy, including the study of mechanics, electricity and magnetism, thermodynamics, and atomic and nuclear physics. It also covers crucial environmental questions that currently are receiving much public attention, such as global warming, radioactive waste, municipal solid waste, and nuclear energy production materials.
The text can be used in physics, technology, physical science, and environmental science courses for non-science majors. Many of the standard topics found in introductory physics textbooks are included. As a result, this book can be used as the text in a conceptual physics course with energy as the central theme. No math or other science prerequisite is necessary. -- From publisher's web site.
Introduction -- Energy mechanics -- Conservation of energy -- Heat and work -- Home energy conservation and heat-transfer control -- Solar energy : characteristics and heating -- Energy from fossil fuels -- Air pollution and energy use -- Global warming, ozone depletion, and waste heat -- Electricity : circuits and superconductors -- Electromagnetism and the generation of electricity -- Electricity from solar, wind, and hydro -- The building blocks of matter : the atom and its nucleus -- Nuclear power : fission -- Effects and uses of radiation -- Future energy alternatives : fusion -- Biomass : from plants to garbage -- Tapping the Earth's heat : geothermal energy -- A national and personal commitment.
Previous edition: 2006.
Includes bibliographical references and index.
Keywords: Power resources -- Environmental aspects; Energy consumption; Energy conservation